Report of the Third Timor-Leste National Aquaculture Forum (NAF3) - Pant, Jharendu; da Cruz Salu, Regio; Bhujel, Ram C.; Teoh, Shwu Jiau; Gomes, Silvino; Timsina, Jagadish (WorldFish, 2024)
The Government of Timor-Leste is committed to developing aquaculture to enhance food security and income opportunities for coastal and inland communities. The Partnership for Aquaculture Development in Timor-Leste Project Phase 2 (PADTL2) (2020–2024) supports the National Aquaculture Development Strategy (NADS) 2012–30 by scaling up Genetically Improved Farmed Tilapia (GIFT) production, targeting 12,000 tons annually by 2030 and increasing fish consumption to 15 kg per person. PADTL2 focuses on improving access to quality seed, feed, and technologies; strengthening fish market chains; and promoting fish consumption through awareness campaigns. Building on phase one (2014–2019), it enhances farmer training and capacity building for stakeholders. Funded by the New Zealand Ministry of Foreign Affairs and Trade (MFAT) and USAID, PADTL2 fosters sustainable aquaculture development in Timor-Leste.